Pulmonary Hypertension in Adult Congenital Heart Disease: From Registry to Policy - Lucia Kris Dinarti (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Pulmonary Hypertension in Adult Congenital Heart Disease: From Registry to Policy